KEPENTINGAN INDIA DALAM MERATIFIKASI PROTOKOL PALERMO TAHUN 2011 - Silitinga, Sophia A. E.; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aim to explain the interest of India to ratify the Palermo Protocol on 2011. India signed the Protocol on 2002, but pending the ratify until nine years. This protocol contain many method to prevent, suppress and punish human trafficking especially woman and children. India is a country which have the highest level of human trafficking. It happen because three factor, such as economic, culture and the geographic condition of India.Protocol Palermo made on November 2000 and published on December 2003. This protocol made for the big purpose for the one and only reference for the world to decreased and prevent the human trafficking caseThis case will be analyzed in nation-state level within realism paradigm and foreign policy theory and also interest concept. The foreign policy theory is the basic of the author to analyzed India make the foreign policy to ratify that protocol.India ratify this protocol to decreased the number of human trafficking victim in India and also to have the international relations among the member of Palermo Protocol. India as the biggest state in South Asia should have a good predicate as a state which can success decreased the human trafficking in India.Keywords: human trafficking, human security, Palermo Protocol